2013
DOI: 10.1681/asn.2012010097
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hypodysplasia Associates with a Wnt4 Variant that Causes Aberrant Canonical Wnt Signaling

Abstract: Abnormal differentiation of the renal stem/progenitor pool into kidney tissue can lead to renal hypodysplasia (RHD), but the underlying causes of RHD are not well understood. In this multicenter study, we identified 20 Israeli pedigrees with isolated familial, nonsyndromic RHD and screened for mutations in candidate genes involved in kidney development, including PAX2, HNF1B, EYA1, SIX1, SIX2, SALL1, GDNF, WNT4, and WT1. In addition to previously reported RHD-causing genes, we found that two affected brothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…1). Moreover, several of the variants identified in our study were close to or in the same domain as those sites reported in previous studies [10,11,17,18] as pathogenic mutations (online suppl. Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1). Moreover, several of the variants identified in our study were close to or in the same domain as those sites reported in previous studies [10,11,17,18] as pathogenic mutations (online suppl. Fig.…”
Section: Resultssupporting
confidence: 86%
“…In 2013, Vivante et al [17] reported a heterozygous missense mutation in WNT4 in 1 of 20 Israeli families with non-syndromic renal hypodysplasia. In the same year, Sanna-Cherchi et al [23] reported the effect of a specific DSTYK mutation in CAKUT.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Wnt9b, Wnt7b, and Wnt4 are indispensable in the inductive signals leading to the epithelia that form the nephron, 30,31 and they are reactivated during renal repair and in renal fibrosis. [32][33][34] In renal repair, Wnt4 stimulation contributes to cellular proliferation and epithelial reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus β-catenin can act as a transcription factor (along with its cofactors TCF/LEF) to promote gene transcription of effectors of Wnt signalling, such as c-myc and cyclin D2. In contrast, the non-canonical pathways, such as those stimulated by Wnt4 are β-catenin independent and have been shown to antagonise the canonical Wnt pathway in several cell types [13,14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%